Synergies across Health, Food & Nutrition, Education, and Empowerment: An SDG-Indicator–Based Analysis of PT Bukit Asam’s Social and Environmental Responsibility Programs - Fatkhullah, Mukhammad; Habib, Muhammad Alhada Fuadilah; Besto, Maestoso; Saputri, Dhea Angie (Prospect Publishing, 2025)
This study examines the performance of PT Bukit Asam’s Social and Environmental Responsibility programs across three pillars—health and nutrition, education, and empowerment and gender—and assesses how far they reinforce one another in support of SDGs 2, 3, 4, and 8. The approach is descriptive–comparative across programs and time (2023–first half of 2025). Analysis relies on annual summaries per program and concise derived measures: service density (beneficiaries per service point), library coverage (schools, students, and teachers engaged), women’s participation (share of female members), and emissions intensity per service point. The strongest synergies arise when programs operate in the same places, calendars are aligned, and common success metrics are used. This pattern appears in the flow from mobile health clinics to supplementary feeding and stunting management (PMT–Stunting); in school-based eye screening delivered alongside the mobile library; in schools serving as hubs to diffuse SIBA (Sentra Industri Bukit Asam) knowledge and products; and in reduced travel and emissions when service routes are combined. Trends from 2023 to the first half of 2025 indicate maintained or rising reach on several components, while shifts in education facility composition and fluctuations in estimated emissions warrant continued monitoring. Practically, the study proposes a shared cross-program metric set—percentage of locations receiving two complementary services, share of participants progressing from screening to the next intervention, time from screening to enrollment, library coverage, women’s participation and per-member productivity in SIBA, and emissions intensity per service point—for decision-making and routine monitoring. This study has limitations related to data availability (2025 covers only the first half), the absence of population size by area for adjusted comparisons, and year-to-year differences in certain indicator definitions. These conditions call for standardizing indicator definitions, completing key variables, and coordinating schedules and sites so cross-pillar benefits become more measurable and cumulative.